Interpretive Research Design: Concepts and Processes - Schwartz-Shea, Peregrine; Yanow, Dvora (Routledge Series on Interpretive Methods, 2012)
Research design is fundamental to all scientific endeavors, at all levels and in all institutional settings. In many social science disciplines, however, scholars working in an interpretive-qualitative tradition get little guidance on this aspect of research from the positivist-centered training they receive. This book is an authoritative examination of the concepts and processes underlying the design of an interpretive research project. Such an approach to design starts with the recognition that researchers are inevitably embedded in the intersubjective social processes of the worlds they study. In focusing on researchers' theoretical, ontological, epistemological, and methods choices in designing research projects, Schwartz-Shea and Yanow set the stage for other volumes in the Routledge Series on Interpretive Methods. They also engage some very practical issues, such as ethics reviews and the structure of research proposals. This concise guide explores where research questions come from, criteria for evaluating research designs, how interpretive researchers engage with "world-making," context, systematicity and flexibility, reflexivity and positionality, and such contemporary issues as data archiving and the researcher's body in the field.